Herbage Yield, Lamb Growth and Foraging Behavior in Agrivoltaic Production System - Andrew, Alyssa C.; Higgins, Chad W.; Smallman, Mary A.; Graham, Maggie; Ates, Serkan (Frontiers in Sustainable Food Systems, 2021)
AAgrivoltaic systems are designed to mutually benefit solar energy and agricultural production in the same location for dual-use of land. This study was conducted to compare lamb growth and pasture production from solar pastures in agrivoltaic systems and traditional open pastures over 2 years in Oregon. Weaned Polypay lambs grew at 120 and 119 g head-1 d-1 in solar and open pastures, respectively in spring 2019 (P =0.90). The liveweight production between solar (1.5 kg ha-1 d-1) and open pastures (1.3 kg ha-1 d-1) were comparable (P =0.67). Similarly, lamb liveweight gains and liveweight productions were comparable in both solar (89 g head-1 d-1; 4.6 kg ha-1 d-1) and open (92 g head-1 d-1; 5.0 kg ha-1 d-1) pastures (all P >0.05) in 2020. The daily water consumption of the lambs in spring 2019 were similar during early spring, but lambs in open pastures consumed 0.72 L head-1 d-1 more water than those grazed under solar panels in the late spring period (P <0.01). No difference was observed in water intake of the lambs in spring 2020 (P =0.42). Over the entire period, solar pastures produced 38% lower herbage than open pastures due to low pasture density in fully shaded areas under solar panels. The results from our grazing study indicated that lower herbage mass available in solar pastures was offset by higher forage quality, resulting in similar spring lamb production to open pastures. Our findings also suggest that the land productivity could be greatly increased through combining sheep grazing and solar energy production on the same land in agrivoltaics systems.